Manajemen Individualized Education Program (IEP) Pada Anak Berkebutuhan Khusus (ABK) di Sekolah Inklusif SDN Kebondalem Mojokerto - Rahelia Amanda; Rahmat R (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Children with special needs are entitled to the same quality education as regular students, including through inclusive education pathways. One of the essential instruments in inclusive education is the Individualized Education Program (IEP), a learning-planning document designed according to the needs, abilities, and characteristics of each child with special needs. This study aims to analyze the management of IEP for children with special needs at the inclusive school of SDN Kebondalem Mojokerto and to identify the supporting and inhibiting factors in its implementation. This research employed a qualitative approach with a descriptive case study design. Data were collected through observation, in-depth interviews with the principal, special assistant teachers, regular homeroom teachers, and parents of children with special needs, as well as documentation. Data were analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing, with credibility established through source, technique, and time triangulation. The findings indicate that IEP management at SDN Kebondalem Mojokerto is carried out through four stages, namely planning, organizing, actuating, and evaluating, implemented through a two-session learning schedule that separates regular and inclusive classes. Supporting factors include the presence of special assistant teachers, collaboration among teachers, principal support, individualized lesson plans, and parental involvement. Meanwhile, inhibiting factors include a limited number of special assistant teachers, inadequate supporting facilities, the absence of external professional involvement, and limited training for regular teachers.